PENERAPAN STANDAR TM-5-623 DALAM PENILAIAN PAVEMENT CONDITION INDEX - Putra, Made Budi Purnama; Birawaputra, Indra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2025)
The pavement condition along Drs. Esau Sesa Road in Manokwari exhibits various forms of distress that have the potential to reduce the overall level of service. This situation necessitates an objective assessment to determine the existing severity of pavement deterioration and to identify appropriate maintenance needs. This study aims to evaluate pavement conditions using the Pavement Condition Index (PCI) method based on the TM-5-623 standard and to identify the predominant types of distress occurring in each sampling unit. The assessment was conducted through visual surveys on 42 sampling units, each covering an area of 300 m², followed by measurements of distress types and severity levels, calculation of density (%), deduct values, and determination of PCI scores for each unit. The analysis revealed variations in pavement condition across both lanes, with PCI values ranging from very poor to excellent. The most prevalent types of distress include polished aggregate, alligator cracking, patching and utility cut patching, as well as weathering and ravelling distresses largely influenced by traffic loading and climatic factors. The non-uniform distribution of pavement deterioration indicates a need for differentiated maintenance strategies for each sampling unit, particularly those with low PCI scores. These findings provide an objective foundation for local government agencies to plan periodic maintenance and rehabilitation efforts, thereby supporting the sustainable improvement of roadway service quality.